Disputas curriculares: o que ensinar de sociologia no ensino médio? - Thiago Ingrassia Pereira (Ciências Sociais Unisinos, 2015)
What should one teach? This a basic question in the definition of the school curriculum that is permeated by ideological disputes. In the midst of polemics, in this article I emphasize the initial training of teachers in the area of social sciences and deal with the debate on the official curriculum versus the real curriculum, reflecting on curriculum theories and betting in the creation of contents that are meaningful for the learning of sociology in basic education.